Oral manifestation of atypical chronic herpes in immunocompromised patients: Case report - Ielo, Nara Maria Vasconcelos; Kalinin, Yuri; Ono, Nancy Miyuki; Dorigo, Loni Suliani; Costa, Anderson Costa Lino; Furtado, Juvencio José Duailibe; Marcucci, Marcelo (Journal of Oral Diagnosis, 2019)
The infection is caused by the herpes simplex virus (HSV) represents one of the most common infections in the orofacial region, and may present in the primary, recurrent forms or more rarely in the chronic form. Due to the high prevalence of HSV in the gen- eral population, this infection is frequently present in immunosuppressed patients, such as opportunistic or co-infected patients. In immunocompromised patients oral lesions may appear as progressive enlargement ulcers, or in unusual forms, such as white-yellow plaques involving extensive areas of the lower lip and oral mucosa. Objective: To report a case of patient immunocompromised, with intra-oral yellowish-white lesion on the mid- line of the tongue was asymptomatic. Case report: Female patient has a history of HIV positive, with abandonment antiretroviral therapy (ART), and pulmonary tuberculosis. The intraoral physical examination revealed yellowish-white lesion on the midline of the tongue, emitting lateral projections with circinate and serpinous borders, with well defined transition area with normal mucosa. Areas of erosion/ulceration at the center of the le- sion projections could be observed. The surface was not removable by scraping, and the lesion was asymptomatic. The immuno-histochemical study confirmed that it is a chronic HSV lesion and the patient is still on tuberculosis treatment and ART is reintroduced. Conclusion: The importance of the dental surgeon inserted in the multidisciplinary hos- pital team, helping the early diagnosis of oral manifestations and efficiency in involution of the clinical picture of the immunosuppressed patient.